A pilot study of user perception on recreational activity in enhancing museum experience / Muhamad Redzuden Mat, Mohd Najib Mohd Salleh and Muhamad Azhar Ghazali - Mat, Muhamad Redzuden; Mohd Salleh, Mohd Najib; Ghazali, Muhamad Azhar (2022)
Museums today play an increasingly essential role in society as a result of their increased position in comparison to their early predecessors. Besides visually appealing displays and exciting exhibits and stimulants, recreational activities may be one of a museum's most essential draws. The purpose of this pilot study is to assess the credibility and reliability of the planned research on the level of users' perceptions in the context of recreational activity in museums before the full paper is implemented. Thorough studies on the role of the museum to accommodate leisure and recreation for the user are done through literature review and users' perceptions are determined and evaluated using a quantitative method, which is measured through the distribution of a structured questionnaire and the data was then analysed using Statistical SPSS. This pilot study revealed the changing role and definition of museums in its literature study and overall users' perception towards museums with a recreational activity is still not yet anticipated by the users for the context of the current local museums but yet the users are hoping for better integration of physical recreational activity within a museum for the better museum experience.